Study on the Influence of LED Spectrum on the Visual and Nonvisual Effects in the Interior Zone of Tunnels - Li-Li Dong; Peng Liu; Qi Lou; Wen-Hai Xu (Journal of Advanced Transportation)
Judicious use of lamps is of profound significance to improve the internal traffic safety of tunnels. This study evaluated the biological effects of spectrum on human visual and nonvisual under mesopic vision category. According to the difference of human eyes’ response to the visual and nonvisual biological effects of different wavelengths of light radiation, a method of applying the mesopic visual spectral luminous efficiency curve to the assessment of nonvisual biological effects and blue light hazards is proposed. The results show that, in theory, under mesopic vision category, the spectrum with high correlation color temperature (CCT) and high color rendering index (CRI) has higher blue light content Z-value and has greater impact on human nonvisual effects and blue light radiation damage, but it can also provide higher human perception luminance. The visual effect detection experiment of driving in the interior zones of the tunnel is simulated in the laboratory, and the critical flicker frequency and reaction time are taken as physiological indexes. The results show that the spectrum with high CCT and high CRI corresponds to lower critical flicker frequency drop value and faster reaction time, which has a positive effect on improving driving safety. Therefore, this paper suggests that the LED with high CCT and high CRI (CCT = 6500 K, CRI2012 = 95) should be used in the interior zones of the tunnel with relatively short lighting section, and the CCT and CRI should be appropriately reduced in other road environments with long lighting section to reduce the impact of spectrum on nonvisual photobiology, so as to improve road traffic safety.